2008
DOI: 10.1086/590248
|View full text |Cite
|
Sign up to set email alerts
|

Particle Acceleration in Relativistic Collisionless Shocks: Fermi Process at Last?

Abstract: We present evidence that relativistic shocks propagating in unmagnetized plasmas can self-consistently accelerate particles. We use long-term two-dimensional particle-in-cell simulations to study the well-developed shock structure in unmagnetized pair plasma. The particle spectrum downstream of such a shock consists of two components: a relativistic Maxwellian, with a characteristic temperature set by the upstream kinetic energy of the flow, and a high-energy tail, extending to energies 1100 times that of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
520
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(585 citation statements)
references
References 25 publications
44
520
0
Order By: Relevance
“…We also note that the model presented by Spitkovsky (2008), in which the shock acceleration process is studied in a selfconsistent fashion, provides results that are consistent with our phenomenological picture. The result from this numerical study is a relativistic Maxwellian, and a high-energy tail with s = 2.4 ± 0.1, plus an exponential cut-off moving to higher energies with time of the simulation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also note that the model presented by Spitkovsky (2008), in which the shock acceleration process is studied in a selfconsistent fashion, provides results that are consistent with our phenomenological picture. The result from this numerical study is a relativistic Maxwellian, and a high-energy tail with s = 2.4 ± 0.1, plus an exponential cut-off moving to higher energies with time of the simulation.…”
Section: Discussionsupporting
confidence: 87%
“…A more careful analysis indicates that such a contradiction is only apparent. As demonstrated by Spitkovsky (2008), diffusive shock acceleration models rely on the presence of a magnetic turbulence close to the shock responsible for the scattering process, although these models do not clearly determine the possible role of turbulence in the acceleration. Our observational analysis appears to indicate the simultaneous roles of the first and second order processes, where the stochastic acceleration arises from the magnetic turbulence and is indicated by the curvature and more generally by the E p − b relation, and the first order is indicated by the slope of the electron power-law tail.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with recent numerical simulations of relativistic collisionless shocks (Spitkovsky 2008), if a significant fraction of the hadrons interacts and generates π 0 .…”
Section: Energetic Considerationssupporting
confidence: 92%
“…This is in agreement with numerical simulations of relativistic shocks, which have demonstrated that diffusive shock acceleration forms such power-law spectra (Achterberg et al 2001;Spitkovsky 2008;Summerlin & Baring 2012). Therefore, shocks are frequently used to explain blazar flaring activities.…”
Section: Introductionsupporting
confidence: 89%